2007
DOI: 10.1186/1475-2867-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Combination of tunicamycin with anticancer drugs synergistically enhances their toxicity in multidrug-resistant human ovarian cystadenocarcinoma cells

Abstract: Background: The pharmacologic modulatory effects of the antibiotic, tunicamycin (TM), on multidrug-resistant human UWOV2 ovarian cancer cells are reported. The UWOV2 cell line was derived from a cystadenocarcinoma in a patient refractory to combination chemotherapy with actinomycin D, vincristine (VCR), cis-diaminedichloroplatinum (II) (CDDP) and doxorubicin (DXR). In an attempt to explain drug resistance in this cell line, we examined the effects of TM on their sensitivity to various anticancer drugs, the upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 94 publications
0
42
0
Order By: Relevance
“…BI is a much simpler and straightforward way of measuring interactions than Loewe additivity, which requires examination of interactions across a gradient of concentrations for each of the drugs. Although Loewe integrates more information about interactions, the ease of measurement and calculation of BI has led to its use in a huge number of studies [8,14,21,29,[45][46][47][48][49], including our present one.…”
Section: Discussionmentioning
confidence: 99%
“…BI is a much simpler and straightforward way of measuring interactions than Loewe additivity, which requires examination of interactions across a gradient of concentrations for each of the drugs. Although Loewe integrates more information about interactions, the ease of measurement and calculation of BI has led to its use in a huge number of studies [8,14,21,29,[45][46][47][48][49], including our present one.…”
Section: Discussionmentioning
confidence: 99%
“…TNM enhances the sensitivity of not only drug-resistant NIH-3T3-MDR cells but also drugsensitive NIH-3T3 cells to P-gp substrates (such as DOX and VCR) or to cisPt, a P-gp-untransportable drug (Hiss et al 1996). These pharmacomodulatory effects of TNM are assumed to be mediated by global inhibition of protein and glycoprotein synthesis and synergistic interaction with antineoplastic drugs (Hiss et al 2007). Hiss et al (2007) also concluded that the ability of TNM to enhance the sensitivity of drug-resistant tumor cells may impact the design and optimization of novel resistance modifiers for combination treatment of intractable neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…These pharmacomodulatory effects of TNM are assumed to be mediated by global inhibition of protein and glycoprotein synthesis and synergistic interaction with antineoplastic drugs (Hiss et al 2007). Hiss et al (2007) also concluded that the ability of TNM to enhance the sensitivity of drug-resistant tumor cells may impact the design and optimization of novel resistance modifiers for combination treatment of intractable neoplasms. Application of TNM increases the cellular level of UDP-N-acetylglucosamine, which was associated with distention of the endoplasmic reticulum and the nuclear membranes (Morin and Bernacki 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Even if using the relatively sensitive drug, such as gemcitabine, doxorubicin, tunicamycin and ifosfamide, the clinical remission rate is only about 10%-20% (Hiss et al, 2007;Chumworathayi, 2013;Pitakkarnkul et al, 2013;Su et al, 2013). Because this group of patients have treated with multiple cycles of chemotherapy, causing hematological and non hematological toxicity accumulation, we chosed only single gemcitabine combined with 125 I-seed implantation treatment as the therapy for patients.…”
Section: Adverse Reactionsmentioning
confidence: 99%